2022
DOI: 10.3390/ph15080906
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vitamin D Metabolism in Hospitalized COVID-19 Patients

Abstract: There is increasing data regarding the association between vitamin D and COVID-19. This study aimed to reveal the alterations of vitamin D metabolism in the setting of COVID-19. We examined 119 adult COVID-19 inpatients and 44 apparently healthy adult individuals with similar serum 25OH-D3 levels as a reference group. The assessment included serum biochemical parameters (total calcium, albumin, phosphorus, creatinine), parathyroid hormone (PTH), vitamin D-binding protein (DBP), vitamin D metabolites (25OH-D3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 67 publications
1
10
0
Order By: Relevance
“…Vitamin D depletion is common in severely ill COVID-19 patients [7]. The connection between abnormal kidney function, abnormal vitamin D metabolism, and hypophosphatemia has been demonstrated in a recent study done by Povaliaeva et al [35]. The authors indicated that patients with severe COVID-19 had abnormal vitamin D metabolism, higher serum creatinine levels, and lower serum phosphate levels [35].…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D depletion is common in severely ill COVID-19 patients [7]. The connection between abnormal kidney function, abnormal vitamin D metabolism, and hypophosphatemia has been demonstrated in a recent study done by Povaliaeva et al [35]. The authors indicated that patients with severe COVID-19 had abnormal vitamin D metabolism, higher serum creatinine levels, and lower serum phosphate levels [35].…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the study of Povaliaeva et al 22 found that severely ill covid-19 patients do not have only low levels of vitamin D but they also have profound abnormalities in the metabolism of vitamin D regardless of the clinical course of the disease. Also, the experimental study of Arora et al 23 provided evidence of the protective role of vitamin D against pulmonary viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of vitamin D deficiency is high among individuals with severe COVID-19 infection [ 40 ]. Povaliaeva et al recently conducted a study that established an association between abnormal kidney function, abnormal vitamin D metabolism and hypophosphatemia ( Table 1 ) [ 41 ]. According to the authors, individuals with severe COVID-19 manifested atypical vitamin D metabolism, increased serum creatinine levels and decreased serum phosphate levels ( Figure 4 ) [ 41 ].…”
Section: Incidence Of Phosphocalcium Metabolism Disorders Related To ...mentioning
confidence: 99%
“…Vitamin D (VD) has been recognized for its significant involvement in various metabolic pathways related to musculoskeletal health [ 41 ]. Previous research has demonstrated that supplementation with VD has been shown to confer advantages in muscle recovery following periods of intense physical activity and tissue damage [ 31 , 50 ].…”
Section: Incidence Of Phosphocalcium Metabolism Disorders Related To ...mentioning
confidence: 99%